Analysis of external support and organizational capacity on electronic commerce adoption impact on small medium business performance - Aris - Mardiyono; Gita Sugiyarti (Serat Acitya, 2023)
This study aims to develop the concept of external support, compatibility and organizational capabilities in increasing the adoption of Electronic Commerce and its impact on the performance of small and medium enterprises. The sample of this research was 123 respondents consisting of small and medium culinary business owners in the city of Semarang, Indonesia. The analysis technique uses Structural Equation Modeling - Amos program version 21. The results show that adoption of electronic commerce is significantly positively influenced by external support, by compatibility, by organizational capability, and by organizational capability, in addition to being significantly positively influenced by adoption of electronic commerce and the performance of small and medium-sized businesses. You may swiftly and effectively rework and reword your material by using paraphraser to take your sentences and make modifications.